Financialisation, distribution & the macroeconomic regimes before & after the crisis: A post-Keynesian view on Denmark, Estonia & Latvia - Petra Dünhaupt; Eckhard Hein (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
Since the early 1980s, financialisation has become an increasingly important trend in developed capitalist countries, with different beginnings, speed and intensities in different countries. Rising inequality has been a major feature of this trend. Shares of wages in national income have declined and personal income inequality has increased. Against this background unsustainable demand and growth regimes have developed and dominated the major economies before the crisis: the "debt-led private demand boom" and the "export-led mercantilist" regime. The current paper applies this post-Keynesian approach on the macroeconomics of finance-dominated capitalism to three Baltic Sea countries, Denmark, Estonia and Latvia, both for the pre-crisis and the post-crisis period. First, the macroeconomics of finance-dominated capitalism are briefly reiterated. Second, the financialisation-distribution nexus is examined for the three countries. Third, macroeconomic demand and growth regimes are analysed, both before and after the crisis.
Keywords: D31; D33; D43; F40; F43; G01; 330; finance-dominated capitalism; financialisation; distribution; financial and economic crisis; Kaleckian theory of distribution